Analisis Arah Pergerakan Aktivitas Ekonomi Jakarta terhadap Daerah Sekitarnya dengan Menggunakan Pendekatan Urban Sprawl - Harmadi, Sonny Harry B.; Yudhistira, MH (UI Scholars Hub, 2008)
The economy of Jakarta which vastly grows has changed its area into a complex and highly dense urbanized area, indicated almost all covered by office blocks, manufacturing activities, and residential area while left relatively small for non-urban activity area. Furthermore, in the last decade, the economy of Jakarta has not only influenced in its administrative area, but also has moved across its surrounding area, such as Bogor, Depok, Tangerang and Bekasi. As a consequence, it has changed the allocation of land using in those areas, from the exertion of rice field using to office, manufacturing and residential activities in such a way that going to show a city face. This process is often called urban sprawl. According to the urban economics theory, there are 3 sectors that can change a region as a new urbanized area which are office, manufacturing, and residential activities. This research try to find how those sectors of the economy of Jakarta influence the land allocation process of its surrounding area. Furthermore, this research will show the sprawling direction from those sectors. For instance, it is found that the office sector sprawls to nowhere.